Penerapan Asas Fiduciary Duty dan Piercing the Corporate Veil Terhadap Tanggungjawab Terbatas Direksi Suatu Perseroan Terbatas di Indonesia dan Amerika - Panalaga, Wayan Bimanda (Universitas Ekasakti, 2023)
Board of directors hold a fundamental role when it comes to company’s growth. When managing a company, board of directors must follow certain guidelines. Fiduciary duty is one of the many rules that board of directors must abide to while managing a company. Ordinarily, board of directors have a perk where they do not personally liable for company loss, but when board of directors neglect their fiduciary duty while taking an action on behalf of the company and that action caused the company to suffer loss or harm, then the board of directors are personally liable and must compensate the loss or harm that the company suffers. This happened due to piercing the corporate veil. This research used normative juridical approach and literature study with secondary data. As a conclusion, the final result of this research showed that fiduciary duty that enacted in Indonesia is slightly differs from America, due to Law Number 40 of 2007 Concerning Limited Liability Company, the Indonesian company law adheres semifiduciary duty, while the American adhere full fiduciary duty. Therefore, the regulation regarding piercing the corporate veil in America is more detailed and broader than the ones in Indonesia.